Gambaran makna happiness pada mahasiswa perantau di luar negeri - Adilah, Marjanah Arifah Rifqoh; Widiasih, Puti Archianti (UIN Maulana Malik Ibrahim Malang, 2023)
Happy students are students who are able to accept everything they experience with positive feelings and emotions. Happiness can also be a barrier to stress and reduce hopelessness and depression. This allows it to be understood whether it has a positive impact on the sustainability of foreign students studying abroad. The research method used in this study is a type of qualitative research. With a phenomenological approach. The subject selection uses purposive sampling which is a sampling method selected based on certain criteria. Respondents are students of Bursa Uludağ University totaling three people. Data collection techniques were carried out by observation and interviews. Data analysis uses coding, categories, themes techniques. The results of this study explain the meaning of happiness for overseas students, the dynamics of being an overseas student, and the driving and inhibiting factors in building enthusiasm for studying abroad. Thus, individuals have many ways to survive in a sad or down state so that they can get back up and find their happiness.KEY WORDS: migrant students; overseas; happinessABSTRAKMahasiswa yang bahagia adalah mahasiswa yang mampu menerima segala hal yang mereka alami dengan perasaan dan emosi positif. Kebahagiaan juga dapat menjadi penghalang terhadap stres dan mengurangi rasa putus asa serta depresi. Hal ini memungkinkan untuk dipahami apakah hal tersebut memiliki dampak positif terhadap keberlanjutan mahasiswa asing yang belajar di luar negeri. Metode penelitian yang digunakan dalam studi ini adalah jenis penelitian kualitatif, dengan pendekatan fenomenologis. Pemilihan responden menggunakan metode purposive sampling yang dipilih berdasarkan kriteria tertentu. Responden adalah mahasiswa Universitas Uludağ sebanyak tiga orang. Teknik pengumpulan data dilakukan melalui observasi dan wawancara. Analisis data menggunakan teknik pengodean, kategori, dan tema. Hasil dari penelitian ini menjelaskan makna kebahagiaan bagi mahasiswa perantau, dinamika menjadi mahasiswa perantau, serta faktor pendorong dan penghambat dalam membangun semangat untuk belajar di luar negeri. Dengan demikian, individu memiliki banyak cara untuk bertahan dalam keadaan sedih atau down agar dapat bangkit kembali dan menemukan kebahagiaannya.KATA KUNCImahasiswa perantau; luar negeri; kebahagiaan Copyright ©2023. The Authors. Published by Psikoislamika: Jurnal Psikologi dan Psikologi Islam. This is an open access article under the CC BY NO SA. Link: CreativeCommons — Attribution-NonCommercial-ShareAlike 4.0 International — CCBY-NC-SA 4.0